2016
DOI: 10.21037/jtd.2016.07.90
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence after sublobar resection in patients with small (2 cm or less) non-small cell lung cancer presenting as a solid-predominant tumor on chest computed tomography

Abstract: Background: Sublobar resection is considered controversial for non-small cell lung cancer (NSCLC) presenting as a solid-predominant nodule. The aim of this study was to identify risk factors related to recurrence in small-sized NSCLC presenting as a solid-predominant nodule. Methods: We conducted a retrospective chart review of 118 patients who were treated for clinical N0 NSCLC sized ≤2 cm and who underwent sublobar resection with clear resection margins. We assigned them to two groups according to radiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
(27 reference statements)
1
9
1
Order By: Relevance
“…Su H et al also found that no difference between lobectomy and limited resection was revealed in the GGO-predominant IA stage adenocarcinoma group [ 18 ]. Similar results could also be found in previous studies [ 23 , 24 ]. However, Ye T et al indicated that wedge resection may be inadequate for invasive lung adenocarcinoma ≤2 cm, with GGO features [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Su H et al also found that no difference between lobectomy and limited resection was revealed in the GGO-predominant IA stage adenocarcinoma group [ 18 ]. Similar results could also be found in previous studies [ 23 , 24 ]. However, Ye T et al indicated that wedge resection may be inadequate for invasive lung adenocarcinoma ≤2 cm, with GGO features [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study found main tumor SUVmax > 2.5 as a risk factor for lymph node metastasis, but its predictive power was far less than previously reported, 14 possibly because GGO demonstrated a relatively lower SUVmax value than solid nodules on PET/CT, thus influencing clinical judgment.…”
Section: Discussioncontrasting
confidence: 95%
“…Several reports have indicated CTR as a valuable prognostic factor. For example, Moon et al reported solid predominant tumor as a significant factor for tumor recurrence in patients undergoing sublobar resection 14 . In our study, all patients analyzed received lobectomy for a primary lung cancer, and all patients with lymph node metastasis had CTR > 60%.…”
Section: Discussionmentioning
confidence: 68%
“…It is therefore important to elucidate optimal criteria for selecting patients for sublobar resection. Previous studies demonstrated risk factors for poor outcomes after sublobar resection [9,24,25]. Wedge resection (vs segmentectomy), microscopic positive surgical margin, surgical margin…”
Section: Discussionmentioning
confidence: 99%